2019
DOI: 10.3390/bioengineering6040115
|View full text |Cite
|
Sign up to set email alerts
|

Tequila Agave Bagasse Hydrolysate for the Production of Polyhydroxybutyrate by Burkholderia sacchari

Abstract: Tequila agave bagasse (TAB) is the fibrous waste from the Tequila production process. It is generated in large amounts and its disposal is an environmental problem. Its use as a source of fermentable sugars for biotechnological processes is of interest; thus, it was investigated for the production of polyhydroxybutyrate (PHB) by the xylose-assimilating bacteria Burkholderia sacchari. First, it was chemically hydrolyzed, yielding 20.6 g·L−1 of reducing sugars, with xylose and glucose as the main components (7:3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Noteworthy, not only the hexose glucose was readily consumed by the strain, but also the pentose xylose was completely depleted until the end of the process [53]. This procedure is analogous to production of other value-added bioproducts from agave bagasse, as shown, e.g., in 2019 by González-García et al for PHA biopolyester production [54]. In addition, sweet sorghum juice, an inexpensive, sugar-rich raw material, was applied for 2,3-BD biosynthesis by Yuan et al, who used a Serratia marcescens strain, another facultative anaerobe.…”
Section: Acetyl Phosphatementioning
confidence: 85%
“…Noteworthy, not only the hexose glucose was readily consumed by the strain, but also the pentose xylose was completely depleted until the end of the process [53]. This procedure is analogous to production of other value-added bioproducts from agave bagasse, as shown, e.g., in 2019 by González-García et al for PHA biopolyester production [54]. In addition, sweet sorghum juice, an inexpensive, sugar-rich raw material, was applied for 2,3-BD biosynthesis by Yuan et al, who used a Serratia marcescens strain, another facultative anaerobe.…”
Section: Acetyl Phosphatementioning
confidence: 85%
“…They used acid hydrolysis to obtain xylose and Burkholderia sacchari to synthesize PHB with a total biomass concentration of 6.13 g/L and an accumulation of 23% in cells. 164 It was also observed that the pretreatment of cellulosic biomass in combination with enzymes led to a higher yield of PHB during the microbial fermentation than that obtained from the biomass only pretreated with sulfuric acid. 136 This could be ascribed to inhibition effects derived from the formation of byproducts due to sugar degradation during acid hydrolysis.…”
Section: Identification and Utilization Of Alternative Feedstocksmentioning
confidence: 98%
“…In 2019 González-García et al reported the use of blue agave bagasse as a lignocellulosic source to produce PHB. They used acid hydrolysis to obtain xylose and Burkholderia sacchari to synthesize PHB with a total biomass concentration of 6.13 g/L and an accumulation of 23% in cells . It was also observed that the pretreatment of cellulosic biomass in combination with enzymes led to a higher yield of PHB during the microbial fermentation than that obtained from the biomass only pretreated with sulfuric acid .…”
Section: Challenges For the Commercialization Of Phasmentioning
confidence: 99%
“…After the removal of those inhibiting phenolics by convenient methods, the detoxified hydrolysate was used as feedstock for PHB production in a two-step batch cultivation process, resulting in a PHB concentration of almost 3 g/L after 122 h of cultivation. This study provides another example how PHA production can be integrated into the production lines of existing agricultural and food-processing industries in order to upgrade existing waste streams to feedstocks for biopolymer production [12].…”
Section: Individual Contributionsmentioning
confidence: 99%